Dermatomyositis with multiple organ involvement: a case report and literature review - Putri, Wayan Julita Krisnanti; Wardiana, Maya; Anindita, Karina; Putri, Adisti Prafica; Kumaladewi, Baiq Ratna; Santosa, Hilda (Explorer Front, 2023)
Background: Dermatomyositis (DM) is a chronic autoimmune disorder characterized by muscle and skin inflammation, a part of the idiopathic inflammatory myositis (IIM). Even though the disease is idiopathic, there are multifactorial factors related to dermatomyositis. This care report aimed to describe a DM case in a male patient to increase the knowledge and management of DM patients. Case description: A 44-year-old Filipino male was referred to the emergency department (ED) of Siloam Hospital Mataram complaining of muscle pain and weakness with skin rashes 3 weeks before admission. Before the skin rash started, he had enlarged femoral lymph nodes in both thighs. The patient was afebrile with normal vital signs and was prescribed ibuprofen and amoxicillin. After that, he experienced skin rashes around his neck and the back of his ears with minimal pruritus. The symptoms worsened, making him unable to open his mouth and hard to breathe. In the ED, he also threw up dark-colored blood twice. Supporting examination showed elevated transaminase, increased LDH, and creatinine kinase. Biopsy results showed a histologic pattern of dermatomyositis. During hospitalization, he received a high-dose systemic steroid, antibiotic, and symptomatic treatment. He was discharged with a good outcome and planned to continue medical treatment in his country. Conclusion: Dermatomyositis is an idiopathic autoimmune disease involving skin and internal organs. It is a multifactorial disease yet with unclear etiopathogenesis. Specific treatment guidelines for DM are not yet established, but initial systemic corticosteroid and additional steroid-sparring agents may exhibit good outcomes.